2021
DOI: 10.24251/hicss.2021.297
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Multicriteria Acceptability Analysis of EV Sharing in Nordic Rural Areas Affected by Seasonal Residence and Counterurbanization

Abstract: Sharing economy and shared mobility has become a widespread trend in urban areas worldwide. Due to lower population density, car sharing, and other shared mobility applications are generally not accessible in rural areas. This paper utilizes a Stochastic Multicriteria Acceptability Analysis (SMAA) method to assess the criteria importance in siting problem of rural electric vehicle (EV) sharing systems. Nordic rural areas are used as a case study in this analysis, and we compare their feasibility to act as a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Alternatively, there could be strategic thinking about how to deal with the "last mile" transportation from the charging station to a desirable location to wait, such as those with public transit, bike-and scooter-sharing programs, or other options. In rural areas with high amounts of tourism and low amounts of vehicle ownership, Einolander and Kiviaho [36], Zorn and Suni [33] suggest that EV sharing systems could be especially relevant, citing examples in Norway and the USA that use app-based platforms to share electric vehicles. This would provide a new solution for tourists from out-of-the-region, province, or country, wherein, currently, EVs are only rarely available to rent from traditionally ICE rental vehicle companies, and at higher prices where they are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, there could be strategic thinking about how to deal with the "last mile" transportation from the charging station to a desirable location to wait, such as those with public transit, bike-and scooter-sharing programs, or other options. In rural areas with high amounts of tourism and low amounts of vehicle ownership, Einolander and Kiviaho [36], Zorn and Suni [33] suggest that EV sharing systems could be especially relevant, citing examples in Norway and the USA that use app-based platforms to share electric vehicles. This would provide a new solution for tourists from out-of-the-region, province, or country, wherein, currently, EVs are only rarely available to rent from traditionally ICE rental vehicle companies, and at higher prices where they are available.…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing market penetration and the rapidly changing policy and infrastructure investment, the implications of the EV transition for tourism, specifically road trips and drive tourism, remain under-researched [9,10,31,33]. Case studies on EV drive tourism in Indonesia [34], New Zealand [35], Norway [36], and the USA [7,35,37] all call for increased research to better understand, prepare for, and accelerate the EV transition. A literature review by Fitt [9] suggested that EVs could instigate fundamental changes to travel, including not just financial concerns over vehicle and infrastructural upgrades at destinations, but trip planning and rethinking symbolic associations between cars and leisure travel.…”
Section: Introductionmentioning
confidence: 99%
“…A GIS-based fuzzy DEMATEL model was utilized for the ecotourism development and area evaluation in Erzurum, Turkey [23], and an evaluation of ecotourism sites in the Black sea region was conducted using AHP and PROMETHEE [24]. For the purpose of supporting EV sharing in rural areas, SMAA was used in the case of Nordic rural areas [25]. Fuzzy AHP was used for solving ecotourism suitability decision-making problems in the case of Babol in Iran [26].…”
Section: Literature Reviewmentioning
confidence: 99%